(untitled) (Journal of the College of Basic Education, 2022)
The study aimed to identify the comparison between regularity and irregularity in playing football for health and recreation after the age of forty in some health and physical indicators. The researcher chose cholesterol and triglycerides as indicators of the level of some health aspects, and the endurance, strength, speed, and flexibility as an indication of the level of some physical aspect. The researcher assumed that regularity in playing football has a better positive effect in improving some health and physical indicators, by compared to peers who are not regular in playing this game. These indicators were identified through some of the tests and checks that were conducted on the members of the research sample. The researcher used the descriptive approach to its suitability and the nature of the research. The research sample consisted of (20) volunteers, ages (40) to (45) years, And on two groups for each group (10) people. The first group plays football regularly, by (3) training units per week, And at the rate of (60) minutes per training unit. As for the second group, they was practiced irregularly, i.e. random and in free time only. After completing the tests on the two groups, the results showed that the regular were better at health and physical indicators than the non-regular, and this achieves the goals and hypotheses of the research. Among the most important conclusions reached by the researcher, The regularity in sports activities, including football after the age of forty, had a positive effect in improving some health and physical indicators. The researcher recommended the necessity to continue practicing sporting activities on a regular basis in a manner that suits the level and capabilities of the body in these ages, for to maintain the safety and health of the body and its freedom from diseases by allocating sufficient time and avoiding randomness and irregularity in practice.